Influence of chitosan coatings with citric essential oil on the shelf-life of minimally processed mango (Mangifera indica L.) (2015)
Demand for minimally processed fruits have increaseddue to their nutritional value and an increasing change inconsumption habits. Physicochemical, microbiological, structuraland sensory changes were determined in minimally processedmangoes (MPM) with chitosan (CH) edible coatings and lemonand orange essential oils (EOL). The MPM was first dipped in citricacid and a texturizing solution and then dipped in CH and lemonor orange EOL coatings. Weight loss, sensory acceptance, totalsoluble solids, total acidity, ascorbic acid, color changes, firmnessand elasticity, and microbiological changes were quantified for11 days of refrigerated storage. The CH and lemon EOL coatinghad more acceptance than the other treatments. No differenceswere found (p0.05) for weight loss, total acidity, ascorbic acid,firmness or elasticity. There was a high amount of total phenolsdue to the EOL composition, as well as a high antioxidant capacityin the early days of storage. This characteristic decreased in thefinal days of the study. There was a decrease in the microbialcharge for the lemon EOL treatment, as compared to the othersamples. The CH and lemon EOL coating helped to maintain theshelf-life of the MPM for 11 days of storage without affecting thesensory acceptance. The CH and Orange EOL coating did nothave an effect on the MPM physicochemical attributes; however,the sensory acceptance was negatively affected with off-flavorsconferred to the MPM.